Seed Rate and Cultivar Effect on Contribution of Vicia sativa L. Green Manure to Soil Amendment under Mediterranean Conditions - Tigka, Evangelia; Beslemes, Dimitrios; Kakabouki, Ioanna; Pankou, Chrysanthi; Bilalis, Dimitrios; Tokatlidis, Ioannis; Vlachostergios, Dimitrios N. (Agriculture (Basel), 2021)
The performance of Vicia sativa L. cultivars and cultivar mixtures used as green manure under two seed rates in a Mediterranean environment was investigated in a split plot design, over the period 2014–2016. Six common vetch cultivars grown in pure stands or in mixtures were established at two seed rates (S1 = 100 Kg ha−1 and S2 = 180 kg ha−1). Growth traits (e.g., plant height, biomass yield, LAI, CGR) were monitored until incorporation into topsoil. The nitrogen (N) concentration of the incorporated biomass along with the decomposition rate were determined, and the effects on the N supply to the soil were evaluated two, four and six months after biomass incorporation. The increment in residual soil Ν four months after green manuring fluctuated from 17 to 45 kg ha−1 among cultivars, and after six months, from 22 to 50 kg ha−1. The average decomposition rate of organic substances was slightly higher for S2 for all time intervals; however the highest value (62.6%) was recorded for S1 six months after biomass incorporation. Seed rate-independent genotypes were identified with regard to the decomposition of organic matter and are suggested as being suitable for green-manuring farming systems with a low seed rate, a fact that offers options with economic and environmental benefits.